The impact of mortality salience and explicit self-esteem on plastic reduction intention: A moderated mediation model - Hsiao-Ling Chiu; Kung-Jeng Wang; Tsang-Hsien Wang (PLoS ONE, 2025)
Mortality salience (MS) and self-esteem affect attitudes and behavioral intentions in various contexts, including pro-environment behavioral intentions. This study aimed to explore how MS and explicit self-esteem impact on attitude towards plastic reduction for future generations (APRFG) and intention to reduce plastic use, by integrating the Theory of Planned Behavior (TPB) and Terror Management Theory (TMT). An experimental design was employed, with 357 participants aged 20 to 70 recruited via an online platform. The participants were randomly assigned to either an MS condition, or a control condition and then measured their explicit self-esteem by the Rosenberg Self-Esteem Scale. Subsequently, the experimental group was exposed to information on the fatal health risks associated with microplastics, while the control group was reminded of their own experiences of dental pain. After a few minutes, all participants were asked to complete a self-report questionnaire, including APRFG, subjective norm, perceived behavioral control, and intention to reduce plastic use. Data were analyzed using the PROCESS macro to examine mediation and moderation effects. Our findings showed that MS significantly enhanced APRFG, subjective norm, and perceived behavioral control, which in turn led to stronger intention to reduce plastic use. Among these three factors, the mediating effect of APRFG was the most pronounced, highlighting its central role in linking MS to plastic reduction intention. MS, when combined with explicit self-esteem, significantly influences APRFG and intention to reduce plastic use. The relationships between MS and APRFG/plastic reduction intention were particularly pronounced among the participants with lower explicit self-esteem. Policymakers can leverage these insights to craft marketing messages that enhance plastic-reduction efforts, taking into account individual differences in explicit self-esteem.